Freshwater Molluscs from Mudbalwa Village Develoment Committee, Rautahat , Nepal - Yadav, Chandra Narayan R.; Subba, Bharat Raj (Our Nature, 2009)
The collection comprised nine of molluscs belonging to six families viz. Viviparidae, Pilidae, Planorbidae, Thiaridae, Amblemidae and Corbilidae. Out of six families, two families viz. Thiaridae and Amblemidae are represented by two species. Keywords: Mollusc, Mudbalwa VDC, Nepal doi: 10.3126/on.v6i1.1660 Our Nature (2008)6:82-83